2018
DOI: 10.5455/javar.2018.e297
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and histological changes of uterine horn of Aceh cattle with repeat breeding

Abstract: Objective: This study aimed to observe the changes in anatomical pathology, histopathology, and histomorphometry of uterine horn in Aceh cattle with repeat breeding (RB). Materials and methods: In this study, five uterine horns were collected from fertile Aceh cattle (N1, N2, N3, N4, and N5) and Aceh cattle with RB (RB1, RB2, RB3, RB4, and RB5). Changes in the anatomical pathology of uterine horn were observed prior to histopathological preparations. The results were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Receptive endometrium is vital for appropriate fetal-maternal communication to establish a successful pregnancy. Bovine endometrium, based on its structure and function, is divided into two layers, namely the basal layer and the functional layer with pseudostratified columnar/simple columnar epithelial cells [ 21 ]. The endometrium undergoes morphological and functional changes throughout the estrous cycle to receive a viable competent blastocyst [ 22 ] and remains under the influence of ovarian hormones (estradiol-17β and progesterone).…”
Section: Proteomics Of Bovine Uterus Milieu To Decipher the Molecular...mentioning
confidence: 99%
“…Receptive endometrium is vital for appropriate fetal-maternal communication to establish a successful pregnancy. Bovine endometrium, based on its structure and function, is divided into two layers, namely the basal layer and the functional layer with pseudostratified columnar/simple columnar epithelial cells [ 21 ]. The endometrium undergoes morphological and functional changes throughout the estrous cycle to receive a viable competent blastocyst [ 22 ] and remains under the influence of ovarian hormones (estradiol-17β and progesterone).…”
Section: Proteomics Of Bovine Uterus Milieu To Decipher the Molecular...mentioning
confidence: 99%
“…Histopathology and culture sensitivity are the major tools to evaluate reproductive issues and infertility. Histopathology better describes the status of endometrial glands, caruncles, inflammatory cell infiltration, hemorrhages, and the thickness of uterine layers (Thasmi et al 2018). Currently, the problem is a limitation of knowledge about the cause of repeat breeding and infertility in buffalo.…”
Section: Introductionmentioning
confidence: 99%
“…This causes subclinical endometritis, which consequently results in fertilization or implantation failure. Thasmi et al (2018) reported the changes in anatomy pathology and histopathology of repeat breeding Aceh cows with endometritis caused by subacute and chronic infections. Various therapies have been applied for repeat breeding cows due to endometritis, including the use of antibiotics and prostaglandins (Drillich, 2006;Hussain et al, 2013;Ahmed and Elsheikh, 2014;Mido et al, 2016;and Szenci, 2016).…”
Section: Introductionmentioning
confidence: 99%